A characterization of the uniform rule without Pareto-optimality - Lars Ehlers (SERIEs - Journal of the Spanish Economic Association, 2011)
We consider private good economies with single-peaked preferences. We show that the uniform rule is the only allocation rule satisfying omega-continuity, no-envy, and one-sided resource-monotonicity. This result strengthens a characterization of the uniform rule due to Thomson (Soc Choice Welf 11:205223, 1994).
Keywords: D63; D71; 330; uniform rule; single-peaked preferences; omega-continuity; Güter; Allokation; Pareto-Optimum; Abstimmungsregel; Theorie